Difference between revisions of "009B Sample Final 1, Problem 7"

From Math Wiki
Jump to navigation Jump to search
 
Line 24: Line 24:
 
|-
 
|-
 
|
 
|
&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">S=\int 2\pi x\,ds,</math>&nbsp; where <math style="vertical-align: -18px">ds=\sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">S=\int 2\pi x\,ds,</math>&nbsp; where <math style="vertical-align: -18px">ds=\sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math>
 
|}
 
|}
  
Line 105: Line 105:
 
|Now, we have &nbsp;<math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math>
 
|Now, we have &nbsp;<math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math>
 
|-
 
|-
|We proceed by using trig substitution.  
+
|We proceed by &nbsp;<math>u</math>-substitution.  
 
|-
 
|-
|Let &nbsp;<math style="vertical-align: -13px">x=\frac{1}{2}\tan \theta.</math>&nbsp; Then, &nbsp;<math style="vertical-align:  -12px">dx=\frac{1}{2}\sec^2\theta \,d\theta.</math>
+
|Let &nbsp;<math style="vertical-align: -2px">u=1+4x^2.</math> &nbsp;  
 
|-
 
|-
|So, we have
+
|Then, &nbsp; <math style="vertical-align: 0px">du=8xdx</math>&nbsp; and &nbsp;<math style="vertical-align: -14px">\frac{du}{8}=xdx.</math>
 
|-
 
|-
|
+
|Since the integral is a definite integral, we need to change the bounds of integration.  
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{\int 2\pi x \sqrt{1+4x^2}~dx} & = & \displaystyle{\int 2\pi \bigg(\frac{1}{2}\tan \theta\bigg)\sqrt{1+\tan^2\theta}\bigg(\frac{1}{2}\sec^2\theta\bigg) d\theta}\\
 
&&\\
 
& = & \displaystyle{\int \frac{\pi}{2} \tan \theta \sec \theta \sec^2\theta d\theta}.\\
 
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
 
|-
 
|-
|Now, we use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.
+
|Plugging in our values into the equation &nbsp;<math style="vertical-align: -4px">u=1+4x^2,</math>&nbsp; we get
 
|-
 
|-
|Let &nbsp;<math style="vertical-align: 0px">u=\sec \theta.</math>&nbsp; Then, &nbsp;<math style="vertical-align: -1px">du=\sec \theta \tan \theta \,d\theta.</math>  
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -5px">u_1=1+4(0)^2=1</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">u_2=1+4(1)^2=5.</math>
 
|-
 
|-
|So, the integral becomes
+
|Thus, the integral becomes
 
|-
 
|-
 
|
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
\displaystyle{\int 2\pi x \sqrt{1+4x^2}~dx} & = & \displaystyle{\int \frac{\pi}{2}u^2du}\\
+
S& = & \displaystyle{\int_1^5 \frac{2\pi}{8} \sqrt{u}~du}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\pi}{6}u^3+C}\\
+
& = & \displaystyle{\frac{\pi}{4} \int_1^5 u^{\frac{1}{2}}~du.}
&&\\
 
& = & \displaystyle{\frac{\pi}{6}\sec^3\theta+C}\\
 
&&\\
 
& = & \displaystyle{\frac{\pi}{6}(\sqrt{1+4x^2})^3+C}.\\
 
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Step 4: &nbsp;
+
!Step 3: &nbsp;
 
|-
 
|-
|We started with a definite integral. So, using Step 2 and 3, we have
+
|Now, we integrate to get
 
|-
 
|-
 
|
 
|
 
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
S & = & \displaystyle{\int_0^1 2\pi x \sqrt{1+4x^2}~dx}\\
+
\displaystyle{S} & = & \displaystyle{\frac{\pi}{4}\bigg(\frac{2}{3}u^{\frac{3}{2}}\bigg)\bigg|_{1}^{5}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\pi}{6}(\sqrt{1+4x^2})^3}\bigg|_0^1\\
+
& = & \displaystyle{\frac{\pi}{6}u^{\frac{3}{2}}\bigg|_{1}^{5}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\pi(\sqrt{5})^3}{6}-\frac{\pi}{6}}\\
+
& = & \displaystyle{\frac{\pi}{6}(5)^{\frac{3}{2}}-\frac{\pi}{6}(1)^{\frac{3}{2}}}\\
 
&&\\
 
&&\\
 
& = & \displaystyle{\frac{\pi}{6}(5\sqrt{5}-1)}.\\
 
& = & \displaystyle{\frac{\pi}{6}(5\sqrt{5}-1)}.\\

Latest revision as of 17:06, 20 May 2017

(a) Find the length of the curve

.

(b) The curve

is rotated about the  -axis. Find the area of the resulting surface.

Foundations:  
1. The formula for the length    of a curve    where    is

       

2. Recall
       
3. The surface area    of a function    rotated about the  -axis is given by

         where


Solution:

(a)

Step 1:  
First, we calculate  
Since  
       
Using the formula given in the Foundations section, we have

       

Step 2:  
Now, we have

       

Step 3:  
Finally,

       

(b)

Step 1:  
We start by calculating  
Since  
       
Using the formula given in the Foundations section, we have

       

Step 2:  
Now, we have  
We proceed by  -substitution.
Let    
Then,     and  
Since the integral is a definite integral, we need to change the bounds of integration.
Plugging in our values into the equation    we get
         and  
Thus, the integral becomes

       

Step 3:  
Now, we integrate to get

       


Final Answer:  
    (a)    
    (b)    

Return to Sample Exam